Advancements, challenges, and future perspectives in developing feline herpesvirus 1 as a vaccine vector - Luo, Xinru; Liang, Ruiying; Liang, Lin; Tang, Aoxing; Hou, Shaohua; Ding, Jiabo; Li, Zibin; Tang, Xinming (Frontiers in Immunology, 2024)
As the most prevalent companion animal, cats are threatened by numerous infectious diseases and carry zoonotic pathogens such as Toxoplasma gondii and Bartonella henselae, which are the primary causes of human toxoplasmosis and cat-scratch disease.Vaccines play a crucial role in preventing and controlling the spread of diseases in both humans and animals. Currently, there are only three core vaccines available to prevent feline panleukopenia, feline herpesvirus, and feline calicivirus infections, with few vaccines available for other significant feline infectious and zoonotic diseases. Feline herpesvirus, a major component of the core vaccine, offers several advantages and a stable genetic manipulation platform, making it an ideal model for vaccine vector development to prevent and control feline infectious diseases. This paper reviews the technologies involved in the research and development of the feline herpesvirus vaccine vector, including homologous recombination, CRISPR/Cas9, and bacterial artificial chromosomes. It also examines the design and effectiveness of expressing antigens of other pathogens using the feline herpesvirus as a vaccine vector. Additionally, the paper analyzes existing technical bottlenecks and challenges, providing an outlook on its application prospects. The aim of this review is to provide a scientific basis for the research and development of feline herpesvirus as a vaccine vector and to offer new ideas for the prevention and control of significant feline infectious and zoonotic diseases.